2020
DOI: 10.3390/ijerph17031015
|View full text |Cite
|
Sign up to set email alerts
|

Improving Organizational Health Literacy Responsiveness in Cardiac Rehabilitation Using A Co-Design Methodology: Results from The Heart Skills Study

Abstract: For health services, improving organizational health literacy responsiveness is a promising approach to enhance health and counter health inequity. A number of frameworks and tools are available to help organizations boost their health literacy responsiveness. These include the Ophelia (OPtimising HEalth LIteracy and Access) approach centered on local needs assessments, co-design methodologies, and pragmatic intervention testing. Within a municipal cardiac rehabilitation (CR) setting, the Heart Skills Study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…A recent study showed promising effects of health literacy interventions, particularly the use of teach-back communication, on medication adherence and disease activity in a rheumatology setting (35). In addition, Ophelia studies in other settings have shown the potential for intervention development using health literacy profiles to achieve organizational change (23,36).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed promising effects of health literacy interventions, particularly the use of teach-back communication, on medication adherence and disease activity in a rheumatology setting (35). In addition, Ophelia studies in other settings have shown the potential for intervention development using health literacy profiles to achieve organizational change (23,36).…”
Section: Discussionmentioning
confidence: 99%
“…The HLQ is useful in surveys, intervention studies, and in uncovering the needs and capabilities of individuals [ 8 ]. Interpretations of HLQ data support decisions on changes in clinical treatments to suit the health literacy needs of patients [ 3 , 20 23 ], develop group or population health literacy interventions [ 24 ] and to assess whether an intervention was successful in promoting health literacy of individuals or groups [ 25 ]. The HLQ covers nine conceptually distinct areas (scales) of health literacy including: Feeling understood and supported by healthcare providers Having sufficient information to manage health Actively managing my health Social support for health Appraisal of health information Ability to actively engage with healthcare providers Navigating the healthcare system Ability to find good health information Understand health information well enough to know what to do.…”
Section: Methodsmentioning
confidence: 99%
“…The growing research topic of organizational health literacy was the level of the social ecological model with the most articles. These articles include "Improving Organizational Health Literacy Responsiveness in Cardiac Rehabilitation Using A Co-Design Methodology: Results from The Heart Skills Study" by Aaby et al [63], which considers how to improve organizational health literacy responsiveness in cardiovascular care. Trezona et al [64] provide a relevant self-assessment tool for organizational health literacy in "Field-Testing and Refinement of the Organisational Health Literacy Responsiveness Self-Assessment (Org-HLR) Tool and Process".…”
Section: Organizational Level: Health Systemsmentioning
confidence: 99%